2014
DOI: 10.2174/157339710904140417125627
|View full text |Cite
|
Sign up to set email alerts
|

Digital Ulcers in Systemic Sclerosis – Frequency, Subtype Distribution and Clinical Outcome

Abstract: Digital ulcers (DUs) are frequent and recurrent complication in systemic sclerosis (SSc) and are the main cause of pain, impaired function of the hand and disability in SSc. The current study is a retrospective analysis of 60 SSc patients (47 patients with limited cutaneous SSc, 8 patients with diffuse cutaneous SSc and 5 patients with overlap syndrome, mean age 54.5±14.2 years, 52 women and 8 men). The frequency and evolution of DUs as well as the applied therapeutic strategies were analyzed. During the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…12 Several studies have reported that fingertip DUs have a higher prevalence than extensor ulcers. [13][14][15] In contrast, Ennis et al, reported that extensor ulcers had a similar prevalence (of 6%) and were as similarly disabling as fingertip DUs. 11 Patients often develop ulcers affecting multiple digits simultaneously, including both fingertip and extensor-aspect DUs.…”
Section: Epidemiologymentioning
confidence: 97%
See 1 more Smart Citation
“…12 Several studies have reported that fingertip DUs have a higher prevalence than extensor ulcers. [13][14][15] In contrast, Ennis et al, reported that extensor ulcers had a similar prevalence (of 6%) and were as similarly disabling as fingertip DUs. 11 Patients often develop ulcers affecting multiple digits simultaneously, including both fingertip and extensor-aspect DUs.…”
Section: Epidemiologymentioning
confidence: 97%
“…11 Patients often develop ulcers affecting multiple digits simultaneously, including both fingertip and extensor-aspect DUs. 15 Despite the availability of a number of advanced therapies to prevent and treat DUs, around one third of patients with SSc may develop recurrent ulceration. 16 Clinical presentation RP is a highly variable symptom complex which results from aberrant digital perfusion.…”
Section: Epidemiologymentioning
confidence: 99%
“…Ischaemic DUs commonly occur on the tips of the fingers(Figure 1) and over the extensor aspect (in particular, over the small joints) of the hands. Several studies have found that fingertip DUs are more common than extensor-aspect DUs [13,14]. For example, in the retrospective study by Lambova et al [14], which included 60 patients with SSc, over a follow-up period of between 6 months to 6 years, incident DUs were observed in around a third(n=21,35%) of patients, and with a predominance of fingertip(n=18/21) compared to extensor(n=5/21) DUs; however, both types could be found simultaneously.…”
Section: Where Do Ssc-dus Occur?mentioning
confidence: 99%
“…Several studies have found that fingertip DUs are more common than extensor-aspect DUs [13,14]. For example, in the retrospective study by Lambova et al [14], which included 60 patients with SSc, over a follow-up period of between 6 months to 6 years, incident DUs were observed in around a third(n=21,35%) of patients, and with a predominance of fingertip(n=18/21) compared to extensor(n=5/21) DUs; however, both types could be found simultaneously. Whereas, in a prospective study, which included 148 patients(15 patients who developed 25 SSc-DUs), the prevalence of both fingertip and extensor DUs was 6% [5].…”
Section: Where Do Ssc-dus Occur?mentioning
confidence: 99%
See 1 more Smart Citation